TELAAH KRITIS TRADISI PEMIKIRAN TEOLOGI DI DUNIA PESANTREN - Khasanah, Uswatun (Jurnal Ilmiah Pendidikan dan Keislaman, 2024)
Theology is a science that studies the basic teachings (fundamentals) of a religion. So this becomes very significant when someone wants to explore the ins and outs of his religion. Because theology is the basic teaching of religion, the attitude of every religious believer is actually obliged to study seriously the theology of the religion he adheres to, so that religious believers will gain a strong understanding and belief that has implications for the determination of faith. Meanwhile, if we study Islam, it is basically divided into two main components, namely aqidah and shari'ah. In approaching the problem of aqidah which concerns aspects of human belief, many are required to use aspects of thinking. In approaching the problem of shari'ah which concerns aspects of behavior, humans are required to use a lot of physical abilities (Sahal Mahfoudh, 1994: 358). It was in this issue of 'aqidah - commonly called kalam or theology - that various interpretations arose between Islamic thinkers which later gave birth to the schools of kalam or theology. In Indonesia, Islamic theology taught is generally theology in the form of tawhid. The science of monotheism is usually less in-depth in discussion and less philosophical. Furthermore, the science of tawhid usually gives one-sided discussions and does not express opinions and understandings from other schools or groups in Islamic theology. And the science of tawhid that is taught and known in Indonesia in general is the school of tawhid according to the Asy'ariah school, so that there is an impression among the Indonesian Islamic ummah, that this is the only theology that exists in Indonesia (Harun Nasution, 1986: ix-x). This fact also occurs in pesantren, where pesantren only "only" study Asharite theology wrapped in Ahlussunnah wa 'I-jamaah theology. We can see this from the theological books studied in pesantren which are merely an explanation of al-Ashari's teachings about the attributes of God and the Prophets (Martin Van Bruinessen, 1995: 155). Asharite theology itself belongs to traditional theology, which takes a position between the extreme of rationalists who use metaphors from the leterlek textualist class. He took a position between the Mu'tazilites and the Jabards, but the "common thread" as a middle ground he took was not very clear. One time he sided with the Mu'tazilites, another time tended to Jabariyah, and other times, took the two opinions of the two opposing schools and compromised (Zainun Kamal, 1995: 131) Indeed, basically the theology that grows and develops in the world of pesantren is strongly influenced by a big mainstream of Islamic theological thought that grows and develops in the Islamic world and becomes a role model for most of the ummah. The theology that became a role model was the theology of Ahlussunnah wa 'I-jamaah, aswaja or commonly called Sunni, which continent was Asharite. This theology is able to be accepted in the pesantren community because at least it has provided a middle ground in various theological schools that developed in Islamic civilization. Apart from this, in the pesantren environment and the wider community, the word Ahlussunnah wa 'I-jamaah has a distinctive connotation. The term is considered to be the term that most dominates the overall self-knowledge of pesantren people and the most basic and the term some pesantren people and certain communities who claim to adhere to it actually do not know, even no less among them there are those who identify the term with Nandlatul 'Ulama (NU). In many aspects, there are often people in pesantren or certain communities who think that those who are not NU citizens are not Ahlussunnah wa 'I-jamaah (Imron Arifin, 1993: 23) This is because the discourse of theological thought in pesantren still does not get a proper place, it is still far behind and the discourse of fiqh thought is almost given full priority in most of the pesantren world. Therefore, in pesantren it is necessary to regrow the tradition of theological thought